2012
DOI: 10.1016/j.jrp.2011.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Forgivingness and subjective well-being in adulthood: The moderating role of future time perspective

Abstract: Abstract:This cross-sectional study tested the hypothesis that future time perspective moderates the association between forgivingness and subjective well-being. Results from a sample of adults (N = 962, 19-84 years) indicate that time perspective and forgivingness were strongly associated with positive affect, life satisfaction and optimism. In support of the hypothesis, forgivingness was more strongly associated with positive well-being for those who perceived their future time as limited as compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
71
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 43 publications
12
71
0
4
Order By: Relevance
“…As a whole, our results align with the stream of studies documenting the benefits of an open-ended future time perspective [2,17,18]. However, we believe that further studies may consider the goals an individual sets as a potential underlying mechanism [4,5].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…As a whole, our results align with the stream of studies documenting the benefits of an open-ended future time perspective [2,17,18]. However, we believe that further studies may consider the goals an individual sets as a potential underlying mechanism [4,5].…”
Section: Discussionsupporting
confidence: 86%
“…Both an open-ended future time perspective and a limited future time perspective have been associated with high well-being [2,4,14,17]. In an attempt to answer why a limited future time perspective can be associated with both high and low well-being, we first replicated the results of Cate and John [7] and demonstrated that the Future Time Perspective Scale [3] is composed of at least two different dimensions, a focus on opportunities and a focus on limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Tse and Yip (2009) indicated that forgiveness of others is positively related to interpersonal adjustment and psychological well-being. Similarly, numerous studies have shown that individuals who forgive transgressions tend to experience greater subjective well-being and psychological well-being (Allemand, Hill, Ghaemmaghami & Martin, 2012;Bono, McCullough & Root, 2008;Chan, 2013;Lawler-Row & Piferi, 2006;McCullough, 2000;Toussaint & Webb, 2005). In addition forgiveness was found related with happiness and more happy individuals tend to forgive more than less happy individuals (Emmons & McCullough, 2003;Friedman, 1992;Maltby, Day & Barber, 2005;Toussaint & Friedman, 2009;Worthington, Berry and Parrott, 2001).…”
Section: Introductionmentioning
confidence: 94%